Prevalence and risk factors associated with Peste des Petits Ruminant (PPR) in Jashore, Bangladesh: Prevalence and risk factors associated with PPR in goat (Research in Agriculture Livestock and Fisheries, 2025)
The FAO and the WOAH are launching a global effort to eradicate Peste des Petits Ruminants (PPR) which causes high morbidity and mortality in small ruminants. PPR is the number one killer disease of goats in Bangladesh. The objective of the study was to determine the prevalence and risk factors associated with PPR in goats in Sharsha, Jashore, from September 2023 to November 2023. Clinically infected 456 goats were examined during this period. The presumptive diagnosis of the PPR diseases was based on the owner’s complaints, clinical history, signs and symptoms, and physical examinations of goats. Statistical analysis was done by Chi-square test, and the P-value was calculated by using SPSS 22 (SPSS, Inc., Chicago, IL). In this study, 97 goats (21.3%) were found to be PPR infected out of 456 visited goats in Upazila Veterinary Hospital. PPR was more observed and significantly more prevalent (